Emotional/Behavioral Problems in Children with Acute Lymphoblastic Leukemia: A Case-Control Study - Shiva Nazari (International Journal of Hematology-Oncology and Stem Cell Research, 2014)
Introduction: Despite achievements in treating acute lymphoblastic leukemia (ALL) in children, its burden on the psychosocial status of patients is not well defined yet. This study aims to determine the impact of childhood ALL on emotional and behavioral pattern of the patients compared to healthy peers as assessed by the Child Behavior Checklist (CBCL). Methods: We studied 100 children with ALL (aged 6-12 years) and 100 healthy sex/age peers as control group. All ALL cases were treated by chemotherapy alone. After being informed by a psychologist, parents in both groups were asked to complete the CBCL form. Final results were then compared between the two study groups. Results: There were no significant differences between the groups regarding the general characteristics. Failure in school performance, restricted group activity and less social relations were significantly higher in the ALL cases. Total competence was also significantly disturbed for the ALL cases. Social problems, attention problems, aggressive behavior, externalization, attention deficit/hyperactivity, conduct and oppositional defiant problems were significantly more prevalent in healthy children. Somatic problems were significantly higher in the ALL cases. Conclusion: Our findings suggest that except for somatic problems, behavioral problems among the ALL cases are significantly less frequent than the healthy peers, which may stem from better care and support from the families. Our unique findings emphasize the need for more research on the psychosocial status of children with cancer in future.